IMMUNE ADAPTIVE MECHANISMS IN NEWBORN CHILDREN WITH INTRAUTERINE PNEUMONIAS - S. N. Beniova; M. S. Polyakova; O. V. Nevmerzhitskaya; N. P. Blokhina; M. G. Shegeda (Медицинская иммунология, 2014)
Abstract. The article presents results of a study concerning the state of cytokine system and 1-acid glycoprotein in infants with intrauterine pneumonias at the days 1 to 3 of their postnatal life. It was shown that imbalance of immune mechanisms in the newborns with intrauterine pneumonia is accompanied by decreased neutrophilic inflammatory reactions, being expressed as neutropenia, low IL-8 levels, and inefficiency of protective/adaptive immune cell functions. (Med. Immunol., vol. 10, N 4-5, pp 473-476).